2014
DOI: 10.1136/archdischild-2013-304090
|View full text |Cite
|
Sign up to set email alerts
|

Weighing children; parents agree, but GPs conflicted

Abstract: GPs are conflicted regarding the acceptability of weighing the child but almost all parents believed it helpful. A minority of obese children responded negatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
0
14
1
Order By: Relevance
“…The majority of parents in this study did not consider schools to be a setting where children’s weight status checks should be undertaken. Further, more than one‐quarter of parents in this study did not want their child’s weight status to be checked every time they visit a GP, which does not support previous study findings where almost all parents (98.6%) found it helpful to have their child’s weight checked at routine care appointments with a GP 20 . Parental concerns about school‐based assessments related to a possible increase of bullying and anxiety among children, and putting too much focus on weight rather than overall health, and these worries are supported by previous research findings 33,34 .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The majority of parents in this study did not consider schools to be a setting where children’s weight status checks should be undertaken. Further, more than one‐quarter of parents in this study did not want their child’s weight status to be checked every time they visit a GP, which does not support previous study findings where almost all parents (98.6%) found it helpful to have their child’s weight checked at routine care appointments with a GP 20 . Parental concerns about school‐based assessments related to a possible increase of bullying and anxiety among children, and putting too much focus on weight rather than overall health, and these worries are supported by previous research findings 33,34 .…”
Section: Discussioncontrasting
confidence: 98%
“…Despite this, evidence among general practitioners (GPs) indicates this rarely occurs 15–17 due to various barriers such as time constraints or concerns about parental reaction 18,19 . However, parents’ attitudes towards weight status assessment of their children may be misunderstood, as was indicated in an Irish observation study among parents (n=434) of 5–12‐year‐olds where more than 98% of parents reported they found it useful when GPs checked their child’s weight 20 . Little is known about Australian parents’ perspectives about the undertaking of this check, which currently results in missed opportunities to identify childhood obesity and consequently a failure to address this health issue early.…”
mentioning
confidence: 99%
“…Previous studies also found that parents do see primary care as an appropriate setting for weight management,4 but that they need to be reassured that GPs will address their child's weight in a non-judgemental, sensitive manner and are able to treat childhood obesity effectively 5. The present study shows that almost 30% of GPs gave lifestyle advice during consultation, but whether they did this in a non-judgemental, sensitive way is unknown.…”
mentioning
confidence: 59%
“…Parental participation and cooperation are key factors in the prevention and management of CO [ 28–32 ]. Parents’ lack of recognition or concern about obesity in children has been one of the main barriers in managing the CO [ 8 , 10 , 11 , 13 , 22 , 33 ]. FPs in our study recommended better cooperation between school and parents and using the power of media to increase awareness in the society.…”
Section: Discussionmentioning
confidence: 99%